2011
DOI: 10.1021/cb200057a
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Basis for Engineered Pyrrolysyl-tRNA Synthetase and the Efficient in Vivo Incorporation of Structurally Divergent Non-native Amino Acids

Abstract: Unnatural amino acids (Uaas) can be translationally incorporated into proteins in vivo using evolved tRNA/aminoacyl-tRNA synthetase (RS) pairs, affording chemistries inaccessible when restricted to the 20 natural amino acids. To date, most evolved RSs aminoacylate Uaas chemically similar to the native substrate of the wild-type RS; these conservative changes limit the scope of Uaa applications. Here, we adapt Methanosarcina mazei PylRS to charge a noticeably disparate Uaa, O-methyl-l-tyrosine (Ome). In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 40 publications
7
110
0
Order By: Relevance
“…Structural analyses have also revealed how mutant PylRS enzymes can accommodate ncAAs that are chemically distinct (50) and larger than Pyl (47), including furan-containing Lys (46) and norbornene-containing Pyl analogs (51). Larger ncAAs are accepted by these PylRS variants by creating larger amino acid recognition pockets with mutations to smaller active site residues, particularly at position 306.…”
Section: Resultsmentioning
confidence: 99%
“…Structural analyses have also revealed how mutant PylRS enzymes can accommodate ncAAs that are chemically distinct (50) and larger than Pyl (47), including furan-containing Lys (46) and norbornene-containing Pyl analogs (51). Larger ncAAs are accepted by these PylRS variants by creating larger amino acid recognition pockets with mutations to smaller active site residues, particularly at position 306.…”
Section: Resultsmentioning
confidence: 99%
“…[124] Wang et al showed that PylRS mutants selective for 56 , 96 , and 97 could be evolved. [125, 126]…”
Section: An Outstanding Genetic Code Expansion Toolmentioning
confidence: 99%
“…However, the Pyl-tRNA is not hardwired for amber codon suppression, and can be adapted to decode a number of other codons (Ambrogelly et al, 2007). In addition, the PylRS has been shown to readily accept a variety of side chain structures (Polycarpo et al, 2006;Yanagisawa et al, 2008;Neumann et al, 2008;Chen et al, 2009;Nguyen et al, 2009;Li et al, 2009;Hancock et al, 2010;Ou et al, 2011;Plass et al, 2011;Takimoto et al, 2011) as well as a set of non-alpha amino derivatives (Kobayashi et al, 2009). This feature makes the PylRS/tRNA pair an ideal candidate for site specific integration of NNAAs.…”
Section: Methods For Evolution Of Aarss and Trnas For Nnaasmentioning
confidence: 99%